An In-depth Examination of Cultural Diversity and its Impact on Service Quality in the Hospitality Industry of Nepal - Kunwar, Chhayan; Tiwari, Pankaj Kumar; Khadka, Kalpana (International Journal of Atharva, 2024)
The study investigated the effects of cultural diversity on organizational performance and consumer satisfaction in the hospitality sector, which was noted for its multicultural staff and customer base. A standardized questionnaire was given to a representative sample of workers in the hotel sector to measure demographic traits, attitudes toward cultural diversity, perceptions of inclusion, and the effects of diversity on business performance and customer happiness. Statistical analysis was conducted on the quantifiable data to identify trends, correlations, and the overall impact of cultural diversity on various aspects of hospitality management. The study’s findings contributed to the existing knowledge on cultural diversity in the hospitality sector, providing insights into strategies and methods that enhance industry efficiency and customer satisfaction. The study emphasized the importance of cultivating a welcoming and inclusive company culture that values diversity, promotes cultural awareness, and harnesses the unique skills and perspectives of employees from diverse backgrounds.